Diatom Phytochromes Reveal the Existence of Far-Red-Light-Based Sensing in the Ocean. Issue 3 (3rd March 2016) - Fortunato, Antonio Emidio; Jaubert, Marianne; Enomoto, Gen; Bouly, Jean-Pierre; Raniello, Raffaella; Thaler, Michael; Malviya, Shruti; Bernardes, Juliana Silva; Rappaport, Fabrice; Gentili, Bernard; Huysman, Marie J.J.; Carbone, Alessandra; et al.
Abstract : Diatom phytochromes (DPH) display high sensitivity to far-red light in the far-red poor aquatic environment, opening new perspectives on signaling mechanisms in the marine realm. Abstract: The absorption of visible light in aquatic environments has led to the common assumption that aquatic organisms sense and adapt to penetrative blue/green light wavelengths but show little or no response to the more attenuated red/far-red wavelengths. Here, we show that two marine diatom species, Phaeodactylum tricornutum and Thalassiosira pseudonana, possess a bona fide red/far-red light sensing phytochrome (DPH) that uses biliverdin as a chromophore and displays accentuated red-shifted absorbance peaks compared with other characterized plant and algal phytochromes. Exposure to both red and far-red light causes changes in gene expression in P. tricornutum, and the responses to far-red light disappear in DPH knockout cells, demonstrating that P. tricornutum DPH mediates far-red light signaling. The identification of DPH genes in diverse diatom species widely distributed along the water column further emphasizes the ecological significance of far-red light sensing, raising questions about the sources of far-red light. Our analyses indicate that, although far-red wavelengths from sunlight are only detectable at the ocean surface, chlorophyll fluorescence and Raman scattering can generate red/far-red photons in deeper layers. This study opens up novel perspectives on phytochrome-mediated far-red light signaling in the ocean and on the light sensing and adaptive capabilities of marine phototrophs.